(untitled) (PerCursos, 2023)
This article aimed to understand intergenerational relationships during social distancing. A qualitative approach was adopted in line with bibliographic and field research, through the application of semi-structured interviews and oral history. The research was developed from the experience of four elderly women. The results point out that these relationships present tensions that allow both ruptures of ties and care and reconstruction of sociability. Finally, exclusive family support reveals the insufficiency of public policies that guarantee support to families in this function, requiring the State to implement the right to care for multiple old ages.